Varsity Show - Keighley, William; Barnes, George; Polito, Sol; Berkeley, Busby; Powell, Dick; Healy, Ted; Lane, Priscilla (The Busby Berkeley Collection, 2010)
A college theater troupe has produced terrible shows for years and is about to be shut down because their ancient director won't change his outdated ways. To save themselves, they hire a down on his luck director from New York (Dick Powell) who so happens to be an alumnus and frat brother. [www.dvdverdict.com]